Victimology analysis of child victims of sexual abuse - Rendie Meita Sarie Putri; Mulyadi Alrianto Tajuddin; Nurul Widhanita Y Badilla; Riez Kifli Kolewora (Priviet Social Sciences Journal, 2025)
Victimology is the study of victims, their victimization causes, and the consequences of victimization. Victims can play a functional role in the occurrence of a crime. Although victims have a role in triggering a crime, they must still receive legal protection for their rights. This study examines victimology and forms of legal protection for child victims of sexual abuse using normative and empirical juridical approaches. The results of this study indicate that the occurrence of a crime cannot be seen solely from the perpetrator's perspective; victims also play a role in the occurrence of a crime. The victim's behavior is a driving factor in the occurrence of sexual abuse. In this case, the sexual abuse of victim NK can be categorized as biologically weak, participating, and provocative. The victim has received legal protection in accordance with Article 64, Paragraph (3) of Law Number 35 of 2014 concerning Child Protection, namely receiving rehabilitation, safety guarantees, and accessibility to obtain information on case developments.